INTEGRATION OF STUDENT ACADEMIC INFORMATION SYSTEMS WITH TELEGRAM BOT AS AN AUTOMATIC ANSWERING MACHINE - Harminto Mulyo; Gunawan Mohammad (Universitas Islam Nahdlatul Ulama Jepara, 2022)
The Student Academic Information System (SIAMA) is web-based software developed to manage students' academic data. In this system, student academic data is processed to make academic information useful for students. However, to access the system requires many steps so that time is less efficient if you have to browse through all the stages. Not to mention the need for internet data quotas that are calculated based on how much content the system downloads and uploads. To speed up access to that information, it can be done by integrating the Telegram Bot service as an automated answering service controlled by robots. Using the PPDIOO method, SIAMA has been successfully integrated as an automated answering machine through the utilization and development of the Telegram Bot PHP Library collaborated with Crontab Linux. From the test results, it is known that the response time from the Bot is indicated at the same hour and minute or < 1 minute which means that the bot execution time is relatively fast.